1971
DOI: 10.1507/endocrj1954.18.451
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Diurnal Periodicity of CRF Activity in Adrenalectomized and Hypophysectomized Rats

Abstract: SynopsisDiurnal variations of CRF activity in the median eminence were observed not only in normal, but also in adrenalectomized and hypophysectomized male rats. The presence of circadian rhythm in CRF activity in the absence of the pituitary and adrenal gland suggests that the circadian rhythmicity of ACTH release is controlled by higher centers. The levels of CRF stores in hypophysectomized rats at any time of the day were markedly more increased than those in adrenalectomized and intact rats. This phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…er apparently drives the rhythm of hypothalamic corticotropin-releasing factor (CRF) content (5), which presumably leads to a daily periodicity in adrenocorticotropic hormone (ACTH) production by the anterior pituitary, and the selfsustained adrenal rhythm is entrained by the oscillating plasma ACTH concentration (3). Richter (2) suggested that the circadian clock would be located somewhere in the hypothalamus of the brain.…”
mentioning
confidence: 99%
“…er apparently drives the rhythm of hypothalamic corticotropin-releasing factor (CRF) content (5), which presumably leads to a daily periodicity in adrenocorticotropic hormone (ACTH) production by the anterior pituitary, and the selfsustained adrenal rhythm is entrained by the oscillating plasma ACTH concentration (3). Richter (2) suggested that the circadian clock would be located somewhere in the hypothalamus of the brain.…”
mentioning
confidence: 99%